2009
DOI: 10.1097/iop.0b013e31819a4255
|View full text |Cite
|
Sign up to set email alerts
|

Normalization of Conjunctival Flora After Dacryocystorhinostomy

Abstract: A few weeks is needed for the conjunctival flora to normalize after dacryocystorhinostomy. The time of normalization is related to the type of bacteria, colony count, and presence of silicone tube.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
30
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 10 publications
1
30
2
Order By: Relevance
“…Owji et al (15) reported that microorganism growth rates in samples from the lacrimal sac and involved and contralateral sides of the conjunctiva in a group of patients with NLDO and chronic dacryocystitis were 100%, 100%, and 97.5, respectively, while those in samples from the conjunctiva of healthy subjects was 82.5%. The same organism was isolated from the lacrimal sac and conjunctiva of the involved side in 90% of patients.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Owji et al (15) reported that microorganism growth rates in samples from the lacrimal sac and involved and contralateral sides of the conjunctiva in a group of patients with NLDO and chronic dacryocystitis were 100%, 100%, and 97.5, respectively, while those in samples from the conjunctiva of healthy subjects was 82.5%. The same organism was isolated from the lacrimal sac and conjunctiva of the involved side in 90% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Coden et al (17) evaluated culture samples from purulent lacrimal sac contents in 236 patients with dacryocystitis who were undergoing DCR and reported that the most common bacteria were S. epidermidis (27.3%) and S. aureus (22.1%), with a positive culture rate of 52%. Owji et al (15) studied lacrimal sac cultures from the involved side and conjunctival cultures from the involved and normal sides of patients with NLDO and chronic dacryocystitis, and they found that the most frequently isolated organisms from the lacrimal sac and conjunctiva of the involved side were S. aureus (47.5% and 47.5%, respectively) and S. epidermidis (22.5% and 20%, respectively). On the other hand, the most frequently isolated organisms from the conjunctiva of the normal side and from that of the control healthy subjects were S. epidermidis (60% and 60%, respectively) and S. aureus (47.5% and 30%, respectively) (15) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations